PENERAPAN UNDERDRAIN BOX STORAGE UNTUK PENANGGULANGAN GENANGAN DAN PENINGKATKAN RESAPAN AIR DI KELURAHAN PENURUNAN - Jhordi Hendarwan; Meilani Belladona; Tri Sefrus (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Decreased Village has an area of 86 hectares with a population of 4946 people. The land located around this area has undergone rapid land use changes since the establishment of the largest shopping center in Bengkulu Province, namely Bengkulu Indah Mall (BIM). The construction of buildings in this area does not pay attention to the waste water disposal system and rainwater drainage, so that during the rainy season this area, especially in front of the BIM, often experiences puddles. Underdrain Box Storage is one of the eco-drainage concepts that can be developed for dense settlements (urban settlements). The technical concept of drainage put forward is that rainwater puddles are channeled through an open channel where at the bottom is given holes arranged in a series along the channel as a function to fill the storage space, where the bottom of the reservoir is directly connected to the soil. The problem in this research is how to apply Underdrain Box Storage to overcome inundation and increase water infiltration in Decrease Village. The purpose of this study was to design an Underdrain Box Storage design to overcome puddles and water infiltration in Decreased Village. The method used in this research is the collection of primary and secondary data as well as analyzing the data, namely hydrological analysis and hydraulics analysis for overcoming inundation and increasing water absorption. The results of the study showed that the planned flood discharge was around 1.2421 m3/s for 10 years. The time needed to absorb water in the Underdrain Box Storage for 44.44 minutes is 0.7997 m3/s, with an infiltration speed of 0.0375 m/s. Underdrain Box Storage dimensions are designs that have a shape above the dimensions of the storage box with a length (B1) of 0.6 m and a height (H1) of 0.3 m, for the dimensions of a storage box accomodation with a length (B2) of 0.8 m and a height (H2) 0.6 m.